Disglucemia asociada a fluoroquinolonas: una revisión estructurada (2018)
ABSTRACT: Fluoroquinolone type antimicrobials can cause hypo or hyperglycemia in certain patients. We performed a structured review about this side effect, searching articles published in English or Spanish with full text access in PubMed/Medline. The following MESH terms were used: Hypoglycemia, Hyperglycemia, Quinolones, Ciprofloxacin, Levofloxacin, Moxifloxacin. Additionally, we evaluated the clinical relevance of potential drug interactions, based on the probability of occurrence and the severity of the interaction effect. We obtained 42 publications about the issue; 22 references were selected, where the severity of the interaction in patients with risk factors was evaluated. Patients receiving antidiabetic medications and with risk factors such as advanced age and renal failure may be more likely to have a severe hypoglycemia. In these patients, this drug interaction should be considered clinically relevant since its risk is high or very high.